Understanding patterns of heterogeneity in executive functioning during adolescence: Evidence from population‐level data. Issue 6 (11th March 2022) - Chaku, Natasha; Barry, Kelly; Fowle, Jillianne; Hoyt, Lindsay Till
Abstract: Executive functioning (EF) is fundamental to positive development. Yet, little is known about how to best characterize constellations of EF skills that may inform disparate associations between EF and behavior during adolescence. In the current study, cross‐validated latent profile analysis (LPA) was used to derive profiles of EF based on measures of inhibitory control, working memory, and cognitive flexibility using data from 11, 672 youth (52.2% male, mean age = 9.91 years) in the Adolescent Brain and Cognitive Development study. Four meaningful EF profiles emerged from the data representing Average EF, High EF, Low Inhibitory Control, and Low EF . Boys, youth from low‐income households, and early developing youth were more likely to be in profiles distinguished by lower EF. Profile membership also predicted differences in externalizing, internalizing, and other problem behaviors assessed one year later. Findings indicate that youth may have distinct constellations of EF skills, underscoring the need for person‐centered approaches that focus on patterns of individual characteristics.